Design of Active Sites on Nickel in the Anode of Intermediate‐Temperature Solid Oxide Fuel Cells using Trace Amount of Platinum Oxides. Issue 8 (19th June 2018) - Rednyk, Andrii; Mori, Toshiyuki; Yamamoto, Shunya; Suzuki, Akira; Yamamoto, Yuta; Tanji, Takayoshi; Isaka, Noriko; Kúš, Peter; Ito, Shigeharu; Ye, Fei
Abstract: Invited for this month's cover is the group of Prof. Dr. Toshiyuki Mori at National Institute for Materials Science (NIMS), Japan. The front cover picture shows the formation of new active sites on Ni in the anode of a solid oxide fuel cell (SOFC), which displays high performance at intermediate temperature. The combination of processing route design, microanalysis, and surface atomistic simulation provides us with a new design paradigm for fabrication of high‐performance SOFCs. Read the full text of the article at10.1002/cplu.201800170 . Abstract : "New innovations often arise in areas that can be considered 'blind spots' in academic research, where established ideas are so completely accepted that they become 'common sense'." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201800170 ).